Prenatal carrier screening for spinal muscular atrophy among pregnant Thai women - Tangshewinsirikul, Chayada; Panburana, Panyu; Prakobpanich, Maneerat; Chareonsirisuthigul, Takol; Dejsuphong, Donniphat; Tim-Aroon, Thipwimol; Khongkhatithum, Chaiyos; Sura, Thanyachai; Tunteeratum, Atchara; Wattanasirichaigoon, Duangrurdee (Frontiers in Medicine, 2025)
ObjectivesTo investigate the acceptance rate for spinal muscular atrophy (SMA) carrier screening among Thai pregnant women, their attitudes toward the prenatal screening, carrier rate, and the frequencies of SMN2 copy numbers.MethodsSingleton pregnant women who aged ≥ 18 years, with a gestational age of ≤ 14 weeks at their first visit, were invited to participate the study. All participants completed the questionnaire: Section I—demographic data. Then, they received a pre-test group counseling, followed by an offer of SMA carrier testing at no cost and completion of the questionnaire: Section II—awareness and attitudes toward the screening and Section III—reasons for their choosing “to have” or “not to have” the screening done. Only those having the test done and undergoing post-test counseling were asked to complete the questionnaire: Section IV—attitudes toward the screening process.ResultsThe preexisting knowledge about SMA was low (30.8%). After pre-test counseling, the majority of participants (94.4%) realized the severity of SMA and its burden to the families, leading to a high acceptance rate for carrier screening at 91.4% (181/198). Most participants (92.4%) agreed to have a fetal diagnosis if they were found to be a couple at risk. The genetic screening revealed a SMA carrier rate of 2.2% (1 in 45), and a high frequency of ≤ 2 copies of SMN2 (98.3%). Four participants were found to be carriers, but none of their partners were carriers, yielding no couples at risk in this study. After disclosure of the screening test result, all the participants expressed a feeling of gladness that they had had the test done. The majority (98%) suggested that SMA carrier screening should be offered to all pregnant women and that the cost of testing should be covered by the government and/or by their health coverage schemes (95.5%).ConclusionThe high acceptance rate and positive attitude toward prenatal SMA carrier was demonstrated among Thai pregnant women. Data from the present study highlight urgent needs for endorsement from professional society and public health policy in advancing the SMA carrier screening program in Thailand.